PENGARUH DIMENSI SINISME DALAM PERUBAHAN ORGANISASI TERHADAP TURNOVER INTENTIONS DI TVRI SUMATERA BARAT: MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Hoiriah, Hoiriah; Nasution, Muhammad Fitrah Panabari; Elyanis, Rafidah; Zaitul, Zaitul (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to examine the effect of organizational change cynicism on turnover intentions, with job motivation tested as a mediating variable among employees in the Technical Division of TVRI West Sumatra. A quantitative approach was employed using total sampling, involving 42 respondents. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The results indicate that cynicism toward organizational change has a positive and significant effect on turnover intentions, and a negative and significant effect on job motivation. However, job motivation does not have a significant effect on turnover intentions and does not mediate the relationship between cynicism and the intention to leave. These findings suggest that negative perceptions of organizational change can directly increase employees’ desire to leave while also reducing their work motivation. Therefore, open communication strategies and participatory management approaches are essential to reduce cynicism and enhance employee retention during organizational change processes.